Real-world efficacy and safety of inetetamab-based therapy in HER2-positive metastatic breast cancer patients with prior exposure to trastuzumab - Duan, Yangyang; Sun, Tao; Chen, Zhanhong; Ouyang, Quchang; Li, Kai; Yan, Min; Lv, Zheng; Li, Zhaohui; Man, Li; Luo, Xu; Dong, Yuyang; Jing, Mingxi; et al. (Frontiers in Oncology, 2025)
BackgroundUntil now there has been no comprehensive data from extensive samples to evaluate the therapeutic potential of inetetamab in metastatic breast cancer (MBC) patients who had a history of trastuzumab treatment. Some previous studies had either small sample sizes from single-center, or partial enrolled patients without prior exposure to trastuzumab. This study aimed to provide a deep analysis of inetetamab-based therapy in this specific population.MethodsA multicenter retrospective study collected clinicopathological data from a total of 500 patients between Jul 2020 and Oct 2023. Progression-free survival (PFS) was estimated as the primary endpoint. Secondary endpoints included objective response rate (ORR), disease control rate (DCR) and adverse events (AEs). The association of risk factors with the effect of inetetamab treatment on PFS was evaluated using Cox proportional hazards regression analysis.ResultsIn the overall cohort, we observed a median PFS of 8.0 months, an ORR of 28.6% and a DCR of 89.2% (median treatment line: third line). Meanwhile, patients who received a combination treatment regime of inetetamab + tyrosine kinase inhibitors (TKIs) + chemotherapy achieved the most prolonged PFS of 9.0 months and the higher ORR of 29.3%. Ki67 index, distant lymph nodes metastasis and treatment strategy were independent predictors of PFS. The most common all-grade AEs were neutropenia (182/500, 36.4%) and leukopenia (157/500, 31.4%).ConclusionsInetetamab was promising in HER2-positive MBC patients who had prior exposure to trastuzumab, offering a new option for patients with a prior failure of trastuzumab.